2016
DOI: 10.1080/01677063.2016.1177048
|View full text |Cite
|
Sign up to set email alerts
|

Motivated state control in larval zebrafish: behavioral paradigms and anatomical substrates

Abstract: Over the course of each day, animals prioritize different objectives. Immediate goals may reflect fluctuating internal homeostatic demands, prompting individuals to seek out energy supplies or warmth. At other times, the environment may present temporary challenges or opportunities. Homeostatic demands and environmental signals often elicit persistent changes in an animal’s behavior to meet needs and challenges over extended periods of time. These changes reflect the underlying motivational state of the animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 138 publications
(153 reference statements)
1
18
0
Order By: Relevance
“…As for other short-term internal states, search behaviors are typically time-limited and reversible [ 10 ]. If a resource is not located within the local environment, a roaming search strategy is often initiated, which is characterized by an outward movement profile [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As for other short-term internal states, search behaviors are typically time-limited and reversible [ 10 ]. If a resource is not located within the local environment, a roaming search strategy is often initiated, which is characterized by an outward movement profile [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Motivated behaviors such as search-states are goal directed, in that they promote specific objectives [ 10 , 38 , 39 ]. Therefore, to rigorously test whether local and outward movement patterns facilitate light-search behavior, we developed two novel phototaxis assays.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hallmarks of arousal include sensitization in the form of enhanced sensory acuity, increased motor activity, and greater reactivity to external stimuli. Arousal is a highly conserved, possibly universal feature of animal nervous systems ( Horstick et al., 2016 , Pfaff et al., 2008 ) and is thought to provide a crucial mechanism through which animals can respond appropriately to their environment. Arousal can be “endogenously generated”; for example, the sleep-wake cycle leads to periods of hyperactive motion and increased neural activity alternating with quiescent periods with lower or altered patterns of neural activity ( Chiu et al., 2016 , Iannacone et al., 2017 , Lebestky et al., 2009 , Turek et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we performed a more detailed analysis and observed an overall diminishment of motor behavior in DA‐treated larvae in both the 5‐min and 30‐min analyses (Figure ). In our previous study, we showed a decrease in the number of GABAergic neurons within the 5 dpf DA‐treated larvae pallium and subpallium, which are regions suggested to be related to motivational states; as well as the pretectum and optic tectum, which are regions suggested to be related to vision (Gahtan, ; Horstick, Mueller, & Burgess, ). Moreover, we observed an increase in the number of GABAergic neurons in the thalamus, which is suggested to be a sensory relay station (Mueller, ).…”
Section: Discussionmentioning
confidence: 85%